Educational Robotics as a Motivational Tool for Students with ASD: A First Impression - Monteiro, Milena; González, Maria Verónica; Burlamaqui, Akynara Aglaé; Burlamaqui, Aquiles (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2020)
This work is the result of a proposal for activities involving Educational Robotics (ER) for students aged between six and seven years, diagnosed with Autism Spectrum Disorder (ASD). The objective was to observe the positive impacts that the ER provides in terms of concentration, social interaction and compliance with rules. The methodology used was based on the Reference Curriculum in Technology and Computing, as well as on the National Common Curricular Base proposed by the Education Ministry of Education Culture of Brazil, being directed to the concepts of spatial orientation, recognition of the writing of the name and creation of stories. The results indicate that ER can be used as a motivational tool in order to promote the participation of students in activities in an engaged manner.